The effect of ageing and gender on calf vascular conductance and fatigue during plantar flexion excercise - Reilly, Heather (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Background: Ageing is a complex multifaceted process, which ultimately results in a reduction in neuromuscular function and exercise tolerance. A reduced vasodilatory function and a slower rate of increase in blood flow (blood flow kinetics) to active skeletal muscles has been implicated as a possible underlying cause of the age- associated reduction in exercise tolerance. On the contrary, a vast number of studies indicate an age-associated enhanced fatigue resistance and muscular endurance. However, to date, no studies have looked at blood flow kinetics and fatigue responses simultaneously using the same exercise protocol in aged participants. Furthermore, the majority of previous research examining age-related vasodilatory function and fatigue parameters have involved cycling, knee extension, elbow or leg dorsiflexion exercise. Although all these exercise modalities are functionally relevant, the plantar flexion exercise modality, which is fundamental for walking and for the maintenance of postural stability has not been examined.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin